NILAI-NILAI MANTRA BERCOCOK TANAM DI DESA CAMPA KECAMATAN MADAPANGGA KABUPATEN BIMA - Irwansyah Irwansyah; Arifudin Arifudin; Kamaludin Yusran (Center of Language and Cultural Studies, 2018)
This study explores the nature of mantra for the rice breeding in Campa Village, Madapangga District the regent of Bima. As the indigenous people belive on the aesthetical and spiritual of the mantra, this study tries to explore how society especially the villagers who mostly are farmers perceive values in the mantra. This syudy used ethnograpy and approached the data analysis using qualitative methods. Five informants having authority in the mantra were interviewed and harvesting rice was used as research setting. Observation, interview and document analysis were the sources of data in this research. This study reveals that aqidah (God trust) values are the most values people believe as the total renderness to Allah as the absolute truth. Reying on Allah wish, people involve activities of plantation rice for success. The second value is syariah (law) from where people rule and apply their social and daily life activities. The third value is moral (akhlak) to maintain their surrounding in peace, safe and sustainable.